Dispositional and argumentative aspects of primacy and recency effects: a return to classical rhetoric - Petrinski, Gerassim (Media and Language, 2020)
The goal of this article is to examine and present the rhetorical applications of two important processes affecting human communication – the primacy effect and the recency effect. They are determined by two major factors – the time period by which are separated the messages, and the time that has the audience to make decision and/or to judge upon the orator’s claim. Different models are proposed for intensification of these effects by expanding or reducing the length of the speech on three main levels – the order of delivering the speeches, the order of presenting the information, and the structure of the argument.
Keywords: primacy effect; recency effect; classical rhetoric; argumentation; stylistics